Sosialisasi Potensi Longsor Di Kecamatan Gunungpati Kota Semarang Sebagai Upaya Peningkatan Kesiapsiagaan Masyarakat - Situmorang, Adolf; Kustirini, Anik; Kusrin, Kusrin; Muldiyanto, Agus; Widiatmoko, Kukuh Wisnuaji (Jurnal Pengabdian KOLABORATIF, 2026)
Gunungpati District is characterized by geomorphological conditions dominated by hilly terrain with moderate to steep slopes. These topographic features, combined with the local geological and hydrological conditions, increase the area's susceptibility to landslides. This Community Service Program (PKM) aimed to enhance community knowledge and preparedness regarding potential landslide hazards in Gunungpati District through a community-based awareness and education program. The program employed educational lectures, interactive discussions, and the distribution of educational materials to residents. The activities were held at the village hall and involved 30 participants from several villages in Gunungpati District. The results demonstrated a significant improvement in participants' understanding of the primary causes of landslides, early warning indicators, and appropriate mitigation measures that can be implemented at the community level. The participants' average knowledge score increased by 52%, rising from 33.75% before the program to 85.75% after its completion. These findings indicate that integrating public awareness sessions with interactive discussions, case study presentations, and visual learning media effectively enhances community understanding of landslide hazards and corresponding mitigation strategies. Consequently, this program provides a practical foundation for strengthening community resilience to landslide disasters in Gunungpati District.
Keywords: Disaster-Resilient Community; Hilly Terrain; Landslide; Mitigation; Slope Failure